Bubble Economics How Big a Shock to China's Real Estate Sector Will Throw the Country into Recession, and Why Does It Matter? - Bryane Michael; Simon Zhao (Lincoln Institute of Land Policy, 2016)
How far do China's property prices need to drop in order to send the country into a recession? What does this question tell us about the way Bubble Economies work? In this paper, we develop a theory of Bubble Economics – non-linear and often “systemic” (in the mathematical sense of the word) forces which cause significant misallocations of resources. Our theory draws on the standard elements of most stories of Bubble Economics, looking at the way banking, construction, savings/investment, local government and equities sectors interact. We find that Bubble Economies' GDP growth can depend on property prices changes differently at different times – depending on risks building up in the economy. We argue that a tacit, implicit Bubble Risk Factor might provide a way of understanding a key variable academics and practitioners omit when they try to explain how economies (mis)allocate resources during bubbles. A 15%-20% property price drop could cause recession, if China's economy resembles other large economies having already experienced property-related asset crises. However, a 40% decline would not be out of the question.
Keywords: D58; N15; L85; G01; 330; China recession; bubble economics; fragility; housing bubble